2020
DOI: 10.1177/1178223420976388
|View full text |Cite
|
Sign up to set email alerts
|

Human Mammary Tumor Virus, Human Papilloma Virus, and Epstein-Barr Virus Infection Are Associated With Sporadic Breast Cancer Metastasis

Abstract: Background: Viral cause of sporadic breast cancer (SBC) has been suggested based on the experimental murine model of mammary tumor caused by mouse mammary tumor virus (MMTV), Epstein-Barr virus (EBV), and human papillomavirus (HPV). While some studies have demonstrated the presence of viral sequences of MMTV, HPV, and EBV in breast cancer cells, others failed. These contradictions may be attributed to the geographical distribution of breast cancer incidence and/or technical variations. In the current study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…PCR is potentially a highly sensitive and specific method to detect EBV DNA (). In this study, the use of PCR confirmed the presence of EBV in breast cancer tissue and was comparable with previous PCR results (Sharifpour et al, 2019;Naushad et al, 2017;Fawzy et al, 2008, Arbach et al, 2006, HassabEl-Naby et al, 2017.EBV was localized to infiltrated lymphocytes rather than malignant breast cells (Khan et al, 2011), Therefore, to depend solely on PCR based studies to determine the relationship between EBV DNA and breast cancer risk is inappropriate in infiltrating lymphocytes (Ballard, 2018;Hamad et al, 2020). Reports have indicated an EBER negative form of EBV infection could be present in breast tumor cells (Ballard, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PCR is potentially a highly sensitive and specific method to detect EBV DNA (). In this study, the use of PCR confirmed the presence of EBV in breast cancer tissue and was comparable with previous PCR results (Sharifpour et al, 2019;Naushad et al, 2017;Fawzy et al, 2008, Arbach et al, 2006, HassabEl-Naby et al, 2017.EBV was localized to infiltrated lymphocytes rather than malignant breast cells (Khan et al, 2011), Therefore, to depend solely on PCR based studies to determine the relationship between EBV DNA and breast cancer risk is inappropriate in infiltrating lymphocytes (Ballard, 2018;Hamad et al, 2020). Reports have indicated an EBER negative form of EBV infection could be present in breast tumor cells (Ballard, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, 60 patients were analyzed for the presence of EBV, of which 68.3% of breast cancer patients were positive for EBV DNA. Different studies reported EBV detection in breast cancer patients worldwide (Hamad et al, 2020). Various studies reported a higher prevalence of viral infections in breast cancer patients than in the control group (Fozuni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a similar study published by Ren et al (2019) which included 3607 BC cases and 1728 controls showed a statistically significant association of BC development and HPV infection (OR = 6.22, 95% CI: 4.25–9.12) [ 94 ]. Interestingly, HPV infection was demonstrated in BC samples but not in the normal tissues [ 95 ]. Conversely, HPV infection was also reported in normal breast samples, though it was significantly decreased compared to BC [ 96 , 97 ].…”
Section: Hpv Infection and Breast Cancermentioning
confidence: 99%
“…Earlier investigations have indicated the presence/copresence of high-risk HPVs, EBV, and MMTV-like virus in human breast cancer worldwide. [35][36][37][38] However, a few studies failed to detect the presence of these oncoviruses in human breast cancer as well as normal mammary tissues. [39][40][41] Based on previous reports depicting the role of HPVs, EBV, and MMTV-like virus in the initiation of various cancers, comprising breast, 19,30,[36][37][38][42][43][44][45] we explored the presence/co-presence of high-risk HPVs, EBV, and MMTV-like virus in TNBC samples in Croatian women.…”
Section: Introductionmentioning
confidence: 99%